Nonsyndromic Facial Asymmetry with Unilateral Condylar Aplasia - Ranganadh Nallamothu; Rama Mohan Kodali; N. Koteswara Rao; Leela krishna Guttikonda; U. Vijayalakshmi (Hindawi Limited, 2013)
Introduction. The temporomandibular joint (TMJ) is the most complex elegantly designed joint in the human body. Abnormal development and growth of TMJ may lead to condyle aplasia present in several syndromes expressions, but it is extremely rare when not connected to any underlying pathological disorder or in conjunction with any syndrome. Objective. A rare case of aplasia of the mandibular condyle is presented, along with 3D computed tomography (3D CT) findings. Conclusion. Based on clinical and radiological findings we suggest the abnormal development of the TMJ as the origin. The 3D CT has provided high-quality images, which made diagnosis and a prompt treatment plan possible.